2019
DOI: 10.1177/1524838019843198
|View full text |Cite
|
Sign up to set email alerts
|

Which Violence Against Women Educational Strategies Are Effective for Prequalifying Health-Care Students?: A Systematic Review

Abstract: Gender-based violence (GBV) is a global public health issue which disproportionately affects women. Health-care providers have an important role in recognizing and addressing GBV in practice, yet research suggests that the issue remains underrecognized, with many qualified professionals reporting lack of confidence and a sense of unpreparedness. Prequalifying GBV educational strategies are inconsistent in both quantity and quality worldwide, and to date, there has been no comprehensive review of those programs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 58 publications
4
28
0
2
Order By: Relevance
“…The availability of guidelines and protocols for care provision at health facilities is fundamental, as is the introduction of and training to appropriately utilize guidelines and protocols. Appropriate and effective IPV educational methods, such as interactive learning and practical applications of learning, may be used [32] after they are adapted to the local context. In this study, there were no associations between educational level, work experience, training opportunities, and the affective domain, such as attitudes toward IPV care.…”
Section: Discussionmentioning
confidence: 99%
“…The availability of guidelines and protocols for care provision at health facilities is fundamental, as is the introduction of and training to appropriately utilize guidelines and protocols. Appropriate and effective IPV educational methods, such as interactive learning and practical applications of learning, may be used [32] after they are adapted to the local context. In this study, there were no associations between educational level, work experience, training opportunities, and the affective domain, such as attitudes toward IPV care.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review on effective educational strategies on GBV included active methodologies, such as single session lectures or seminars, interactive online tutorials, standardized patient interactions, peer education, theater, group discussion, role play, and a full-day interactive workshop covering theory and practice [ 31 ]. This review suggested that interactive educational strategies were better than theory-based strategies, as they focused on practical application for learning [ 31 ]. In this sense, a high-fidelity clinical simulation methodology accomplishes this requirement.…”
Section: Introductionmentioning
confidence: 99%
“…Diverse pedagogy and methods of engagement could prove worthwhile in future iterations of the subject. Interactive engagement and training over longer periods of time, including simulated patient encounters, may enhance student learning (Sammut et al, 2019).…”
Section: Future Learningmentioning
confidence: 99%